Action recognition using attention-based spatio-temporal VLAD networks and adaptive video sequences optimization - Zhengkui Weng; Xinmin Li; Shoujian Xiong (Scientific Reports)
Abstract In the field of human action recognition, it is a long-standing challenge to characterize the video-level spatio-temporal features effectively. This is attributable in part to the inability of CNN to model long-range temporal information, especially for actions that consist of multiple staged behaviors. In this paper, a novel attention-based spatio-temporal VLAD network (AST-VLAD) with self-attention model is developed to aggregate the informative deep features across the video according to the adaptive deep feature selected. Moreover, an overall automatic approach to adaptive video sequences optimization (AVSO) is proposed through shot segmentation and dynamic weighted sampling, the AVSO increase in the proportion of action-related frames and eliminate the redundant intervals. Then, based on the optimized video, a self-attention model is introduced in AST-VLAD to modeling the intrinsic spatio-temporal relationship of deep features instead of solving the frame-level features in an average or max pooling manner. Extensive experiments are conducted on two public benchmarks-HMDB51 and UCF101 for evaluation. As compared to the existing frameworks, results show that the proposed approach performs better or as well in the accuracy of classification on both HMDB51 (73.1% ) and UCF101 (96.0%) datasets.